The Forearm’s Subcutaneous Venous Network to Accelerate Maturation of Native Arteriovenous Fistula: A Case Report - Maciej Gołębiowski; Mariia Chumadevska; Mariusz Kusztal; Mirosław Banasik; Tomasz Gołębiowski (Case Reports in Nephrology and Dialysis)
Introduction: A common complication of arteriovenous fistula (AVF) is thrombosis in the venous segment, which can impair vascular access unless a successful thrombectomy is performed. Case Presentation: In this manuscript, we describe the case of a diabetic patient who had primary AVF in a snuff-box with subsequent superficialization of the medial vein of the forearm. Unfortunately, this section of the vein was occluded, although the fistula was patent through the cephalic vein (CV). Due to insufficient flow, this vascular access was unsuitable for hemodialysis. Using a vein from the subcutaneous venous network (SVN), additional AVF was performed. Our goal was to accelerate maturation by doubling arteriovenous flow, which then increased the size of the CV in the arm. After maturation, a second superficialization was performed on the arm, which allowed for successful cannulation. Conclusion: SNV may be considered for the creation of a new AVF to improve the maturation of the primary fistula.